2016
DOI: 10.1590/s0080-623420160000700009
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with glycemic control in people with diabetes at the Family Health Strategy in Pernambuco

Abstract: Objective: Identifying factors associated with glycemic control in people with type 2 Diabetes Mellitus (DM) registered in the Family Health Strategy (FHS) in Pernambuco, Brazil. Method: Associations between glycemic control (glycosylated hemoglobin A lower or equal to 7%) presented by people with DM and variables related to sociodemographic conditions, lifestyle, characteristics of diabetes, treatment and follow-up of patients by health services were investigated by multiple regression. Results: More than 65%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
2
10
0
5
Order By: Relevance
“…The current study showed a high prevalence (77.8%) of inadequate glycemic control (HbA1c>7%) as well as a high mean (8.5%) above the recommended level of HbA1c<7% in Type 2 diabetes mellitus patients studied. The findings of the study are in agreement with other studies conducted in Type 2 diabetes mellitus patients that showed higher mean of HbA1c above 8% as well as high prevalence's of > 60% of poor glycemic control (HbA1c>7%) [21,22].…”
Section: Resultssupporting
confidence: 92%
“…The current study showed a high prevalence (77.8%) of inadequate glycemic control (HbA1c>7%) as well as a high mean (8.5%) above the recommended level of HbA1c<7% in Type 2 diabetes mellitus patients studied. The findings of the study are in agreement with other studies conducted in Type 2 diabetes mellitus patients that showed higher mean of HbA1c above 8% as well as high prevalence's of > 60% of poor glycemic control (HbA1c>7%) [21,22].…”
Section: Resultssupporting
confidence: 92%
“…This affirmation can be justified by the high glycemic levels and glycated hemoglobin present in this sample, in addition to the chronic complications identified. Research on the factors associated with glycemic control found a greater probability of inadequate glycemic control in people with a longer diagnosis of the disease, with fewer referrals to endocrinologists and with complex pharmacological therapy (9) . Thus, the need to revert negative beliefs against the disadvantages of established therapy is reinforced.…”
Section: Discussionmentioning
confidence: 99%
“…The low integration of health professionals with patients is indicated as one of the factors that negatively influences the knowledge and acceptance of the disease and, consequently, inadequate adherence to the treatment. Care management must be co-responsibility between health team and users, with accessibility to a sensitive and motivational dialogue (9) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations